The Impact of Virtual Reality on Collaborative Learning in Higher Education - Aceng Haetami; Omar Khan (International Journal of Educational Narratives, 2024)
The rapid advancement of technology has led to the integration of Virtual Reality (VR) in various sectors, including education. In higher education, collaborative learning is a key element in enhancing student engagement and learning outcomes. However, traditional learning environments face limitations in fostering effective collaboration among students. Virtual Reality offers innovative solutions by creating immersive and interactive environments that can bridge the gap between physical and virtual spaces. This study aims to investigate the impact of VR on collaborative learning in higher education, exploring how VR technologies influence student interaction, engagement, and overall learning outcomes. The research uses a mixed-methods approach, combining qualitative interviews with students and faculty and quantitative data through surveys. The study focuses on students who participated in VR-based collaborative learning activities across different disciplines. Preliminary results indicate that VR enhances communication, problem-solving, and teamwork among students, fostering a more engaging and productive learning experience. Additionally, students reported increased motivation and a deeper understanding of complex concepts through the immersive nature of VR. The study concludes that VR is a valuable tool for enhancing collaborative learning in higher education, offering potential for wider application in various academic fields. Further research is recommended to explore the long-term effects of VR in educational settings and its scalability across diverse institutions.